1969
DOI: 10.12669/pjms.324.10094
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age on The Outcome of Renal Transplantation: A Single-Center Experience

Abstract: Objectives:To analyze the effects of old age on renal transplantation (Tx) results and graft survival, and compared elderly patient population with the young patients.Methods:A total of 1946 renal transplant were performed from 1537 living and 409 cadaveric donors between 2003 and 2014. The recipients were divided into two groups according to their age at the time of transplantation. The young age group consisted of 18-59-year-old, and the elderly group consisted of the ones ≥ 60 years.Results:Acute rejection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 11 publications
2
13
0
1
Order By: Relevance
“…10 Another study also found the 5-year survival rate of kidney transplant subjects in the non-geriatric category was 90% compared to the geriatric category survival of 82%. 11 In this study, the geriatric subjects were found to have higher 5-year survival outcomes (94.7% vs 89.5%). The explanation for this result could be that geriatric patients have a lower chance of rejection due to a weaker immune system, leading to less immunosuppressive therapy.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…10 Another study also found the 5-year survival rate of kidney transplant subjects in the non-geriatric category was 90% compared to the geriatric category survival of 82%. 11 In this study, the geriatric subjects were found to have higher 5-year survival outcomes (94.7% vs 89.5%). The explanation for this result could be that geriatric patients have a lower chance of rejection due to a weaker immune system, leading to less immunosuppressive therapy.…”
Section: Discussionmentioning
confidence: 57%
“…10 This is yet to be elucidated, but the latest study has found that acute graft rejection was found higher in non-geriatric patients, further supporting the role of the lower immune system in geriatric patients survival. 11 Distribution of age between the subjects is also a confounding factor that needs to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest, like other studies evaluating the effect of race on renal transplant outcomes, that the Asian Hmong population on the whole had a reduced degree of sensitization, which may result in reduced rejection risk, and overall lower immunosuppressive burden which translates into favorable infection and patient and graft survival rates . Finally, younger age at time of transplant is thought to be associated with reduced complications after transplant and improved survival outcomes . However, the disparities between the study populations alone do not explain the non‐inferior outcomes in the Hmong population.…”
Section: Discussionmentioning
confidence: 99%
“…triggering postoperative DGF is higher. 20,21 The risk of DGF is also proportional to R-BMI. Hill et al 22 reported that obese patients (BMI≥30kg/m 2 ) are more likely to suffer from DGF than normal patients (18.5kg/m 2 -≤BMI≤24.9 kg/m 2 ).…”
mentioning
confidence: 99%